Career indecision and career indecisiveness in high school and vocational training students: a scoping review - Mata-Correas, María; Hernández-Franco, C Vicente; Prieto-Ursúa, María (Educación XX1, 2025)
Recent events underscore the need for inclusive and sustainable vocational guidance adapted to a context marked by uncertainty, digitalization, stress, and disruptions in the spaces in which adolescents develop. It is key to understand the difficulties that this population may manifest in their transitions, to make vocational decisions. Utilizing the PRISMA-Scr statement, this scoping review examined the literature published between 2007 and 2023 related to the factors that influence career indecision and career indecisiveness, the existing instruments used to measure them in the adolescent population, and the intervention programs applied in their prevention or treatment. Following the predetermined inclusion criteria, 78 papers (N = 825) identified in indexed journals were analyzed. The CIPP-C method was applied for the analysis, which allowed us to present the results in an integrative multidimensional model that would enable us to conjecture the possible relationships between the systems of variables identified, which is one of the main contributions of this work. The results found highlight the heterogeneity of contextual, cognitive, emotional, behavioral, and personality factors in both indecision types, the reliability and validity of unidimensional and multidimensional instruments at a cross-cultural level to assess them, and the presence of intervention programs on developmental career indecision in educational settings. It is concluded that further research is needed for specific evidence-based programs for those with career indecisiveness and for vocational training students. Additional research is also needed for greater representation of qualitative and mixed studies, which collect the experience of undecided students in globalized, digitalized, climatic, and health emergency contexts. Finally, as implications for practice, a narrative, cognitive-behavioral, and systemic approach is recommended. Moreover, specific elements are proposed for intervention in career indecisiveness.